1989
DOI: 10.1159/000460974
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Immunological Characteristics of Maternal Anti-Rh(D) Antibodies in Predicting the Severity of Haemolytic Disease of the Newborn

Abstract: A number of factors were analyzed for their predictive value in indicating the severity of haemolytic disease of the newborn (HDN) in 72 infants. The factors investigated were: maternal antibody titre in the indirect antiglobulin test, the number of antibody molecules on sensitized standard red cells evaluated by a radiometric antiglobulin test, the IgG subclass specificity and the reactivity in monocyte-monolayer assay (MMA) and in the rosette assays with lymphocytes and granulocytes from healthy individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
6
12
1
Order By: Relevance
“…Significantly higher activ ity of IgG2 was present in one serum. Our data are in agreement with the studies of Zupanska et al [11]: that IgG2 and IgG4 antibodies may be produced. In our study out of 107 patients 7 had exclusively IgG2 and/or IgG4.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Significantly higher activ ity of IgG2 was present in one serum. Our data are in agreement with the studies of Zupanska et al [11]: that IgG2 and IgG4 antibodies may be produced. In our study out of 107 patients 7 had exclusively IgG2 and/or IgG4.…”
Section: Discussionsupporting
confidence: 94%
“…Mothers pos sessing exclusively IgG3 anti-D showed a direct correla tion between Rh titre and severity of HDN. Our data seems to be consistent with Zupanska et al [11], who sug gested that the combined presence of IgGl and IgG3 leads to very severe disease. In the present study the still birth rate was 34.8% when the maternal anti-D had a combina tion of IgGl and IgG3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have failed to demonstrate a direct association between the amount of red cell alloantibodies in maternal serum and the severity of HDN. 15,16 The same seems to be true for platelet alloantibodies, as a large prospective study found no correlation between the titre of anti-HPA-1a and severity of FNAIT, 17 although contrasting data have been published. 18,19 One striking explanation for this noncorrelation between maternal alloantibody titre and severity of fetal/ neonatal disease would be a differentially effective transport of IgG alloantibodies across the maternal-fetal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, defining mild to moderate hdn is difficult and many of the controversies around the ability of different assays to predict hdn may partly lie in the criteria used to define hdn by different centres. in good hands, to be a good predictor of severity [10,19], while others have found that the ADCC, using either monocytes [9,13] or lymphocytes [20] as effector cells is better and yet, others rely heavily on a CL assay [21,22], There seems to be a good correlation between the quantity of cell bound IgG subclass of the maternal anti-D and its behaviour in the bioassays: ADCC activity and severity of hdn were correlated with the number of cell bound IgG 1 molecules whereas MMA activity, which was not as closely correlated with severity of hd, was most closely correlated with the number of cell-bound lgG3 [13].…”
Section: Introductionmentioning
confidence: 99%